Jaranan : the Horse Dance and Trance in East Java. - Groenendael, Clara van (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde., 2008)
The dramatic genre of the horse dance (jaranan) is part of an age-old Javanese tradition displaying wide local and regional variations. A striking feature of the performances of the majority of horse dance groups is the appearance of trance dancers. These are used as a means of establishing contact with the spirits of the ancestors, who continue to play an important part in the lives of their descendants as moral beacons in the solution of problems and the fulfillment of wishes. As a consequence of the modernization of society in almost every aspect of life, vigorously propagated as it was by.